Bilingualism and Diglossia in the Canadian Eastern Arctic - Dorais, Louis-Jaques (ARCTIC, 1989)
In the Eastern Arctic the Inuktitut language is as strong as it has ever been in terms of public recognition. But there are some reasons for concern: code-switching, subtractive bilingualism, etc. This article addresses this apparent contradiction by explaining the current language situation as a linguistic conflict. The social history of the Arctic has induced a basic inequality between English, the dominant speech form, and Inuktitut. This situation, called diglossia, entails a gradual loss of the native language among the younger generations. The study of a sample of Inuit students shows that Inuktitut is still the preferred language for addressing one's parents, but it is much less so, especially in the Baffin region, with siblings and friends. It is argued that only a change in the social and political conditions of the Inuit could reverse this trend.Key words: Inuktitut, language (Inuit), bilingualism, diglossia, Eastern Arctic Mots clés: inuktitut, langue (inuit), bilinguisme, diglossie, Arctique de l’est